Evaluating the Association Between Ambient Pollutants and Climate Conditions in Chiangmai, Thailand - S. Piyavadee, R. Chumaporn and V. Patipat (Nature Environment and Pollution Technology)
The most significant air pollutant is particulate matter of less than 10 microns (PM10), followed by ozone (O3) during the monitoring period from 2006 to 2022 in Chiangmai. The association between ambient pollutants and climate conditions in Chiangmai was assessed using regression analysis and analysis of variance (ANOVA). The ANOVA analysis indicated that the average temperature was associated significantly with the nitrogen dioxide (NO2) concentration in the ambient, but the average rainfall volume was associated significantly with most pollutants except only sulfur dioxide (SO2). From the prediction models, the rise in average temperature affected to increase in the concentrations of PM10 and O3. Interestingly, the increase in rainfall will be advantageous to compromise the severity of all pollutants. Meanwhile, on hotter days should be careful of the rise of PM10 and O3 concentrations. Therefore, the vital meteorological variables associated with air pollution are very useful for forecasting the harmful and severity level of each air pollutant.